RF sputtered in-plane NiO-based lithium-metal microbattery - Tleukenov, Yer-Targyn; Yegamkulov, Mukagali; Raiymbekov, Yessimzhan; Nurpeissova, Arailym; Bakenov, Zhumabay; Mukanova, Aliya (Eurasian Journal of Physics and Functional Materials, 2026)
The goal to further increase energy and power density of conventional two-dimensional (2D) structured lithium-ion batteries (LIBs) is driving research towards more complex three-dimensional (3D) batteries with large surface area and accordingly high active material mass loading. So far, many attempts have been implemented to prepare 3D structured LIBs. A highly developed 3D surface allows for a larger amount of active material to be deposited while maintaining a smaller thickness, thus avoiding the challenges associated with a thick electrode. Herein, this paper presents development of in-plane type 3D NiO thin film electrodes produced by radio frequency (RF) magnetron sputtering. The physico- and electro-chemical properties were studied depending on the post-annealing temperature which was in the range of 200-300 0C. It was shown that an in-plane NiO thin film anode with GPE can be developed to enable battery operation without the use of a commercial separator. As a gel-polymer electrolyte (GPE) was used poly(ethylene oxide)-poly(vinylidene fluoride) (PEO-PVDF-co-HFP). The in-plane 3D battery with PEO-PVDF-co-HFP GPE exhibited outstanding cycling stability of 60 cycles, delivering a capacity of 510 mAh g-1. The developed 3D battery, as a result, demonstrated improved cycling stability and electrochemical performance while effectively operating at 0.1C rate. Recommended Citation Tleukenov, Yer-Targyn; Yegamkulov, Mukagali; Raiymbekov, Yessimzhan; Nurpeissova, Arailym; Bakenov, Zhumabay; and Mukanova, Aliya (2024) "RF sputtered in-plane NiO-based lithium-metal microbattery," Eurasian Journal of Physics and Functional Materials: Vol. 8: No. 3, Article 3. DOI: https://doi.org/10.69912/2616-8537.1226